Pemberdayaan UMKM Kuliner Melalui Digitalisasi dan Inovasi Produk di Desa Margoanyar - Anabela, Cindy; Krisna, Melan Candra; Badiah, Roudlotul; Musthofa, M Mutammam; Indira, Irma (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The Community Service Program (KKN) 05 ITBADLA in Margoanyar Village focused on empowering MSMEs through digitalization and product innovation. The main problems faced by MSMEs include limited digital literacy, unattractive product packaging, and marketing that still relies on local networks. The activity method uses a Participatory Learning and Action (PLA) approach through direct mentoring, social media management training, business location integration with Google Maps, and packaging design improvements. The results of the activity show an increase in the ability of MSMEs to promote products digitally, the creation of a stronger visual identity, and increasing the accessibility of business locations for consumers. However, mentoring is still needed so that MSMEs can implement digitalization consistently.